Enhancing Air Compliance of loud speaker cabinet by using Activated Carbon Felts - Jakkaraju, Shashikumar; Radhika. G; NikhilRaj; JohnPaul (International Journal of Psychosocial Rehabilitation, 2020)
At present Fiber glass material is used as stuffing material in sub-woofer cabinet enclosures. It increases Air Compliance and increase the apparent volume of the cabinets since it has properties of sound absorption and insulation. Air Compliance has direct impact on frequency response of the cabinet. By changing air Compliance we can optimize the response. Activated carbon felt can be used in the place of fiber glass because of large absorption coefficient at lower frequency due to adsorption property. Activated carbon Felt have large porosity and large surface area. It is observed Activated carbon felt of range 10 to 15 mm has large absorption coefficient at lower frequencies. The excess absorption of sound energy is due to surface reactance.